The effect of leader-member exchange (LMX) on the relationship between motivating language (ML) dimensions and management effectiveness of Waqf properties by Waqf institutions in Malaysia - Sharfizie Mohd Sharip (2020)
This study empirically examines the effects of leader-member exchange on the relationship between the three dimensions of motivating language namely direction-giving language, empathetic language and meaning-making language and the management effectiveness of Waqf properties by Waqf institutions in Malaysia. Sullivan bases the dimensions of motivating language used in this study on the Theory of Motivating Language. This study employs a quantitative approach through the survey research design. A total of 168 employees out of the overall total of 216 employees in Waqf institutions throughout the country were randomly selected using the random cluster sampling technique for determining the sample size based on the Waqf institutions in each state in Malaysia. In terms of the research instrument, this study employed the Motivational Language Scale adapted from Mayfield and Mayfield the Leader-Member Exchange Scale adapted from Liden et al., and the Management Effectiveness scale adapted from Siti Alawiyah. The findings showed that the model was significant with the value of R squared is 0.443, and p < 0.05. Specifically, the effects of direction-giving language (DGL) (. = ..435. p<0.05) and meaning-making language (MML) (. = ..180. p<0.05) on management effectiveness (ME) are positive and significant. Meanwhile, the effect of empathetic language (EL) (. = ..154. p > 0.05) is positive but not significant. The results of the moderating effect of LMX showed that only the path from empathetic language (EL) to management effectiveness (ME) (.=-0.171, p<0.05) is statistically significant, but the coefficient showed a negative beta value, which indicates an adverse relationship. This means that higher mean of LMX does not lead to higher management effectiveness when the leader applies a high level of empathetic language usage. In conclusion, high power distance cultures such as that of Malaysia, only direction-giving language and meaning-making language usage among leaders can lead to the creation of management effectiveness, whereas the usage of empathetic language is unsuitable due to the high social distance. Meanwhile, a higher dyadic relationship via leader-member exchange does not strengthen the effect of the three types of motivating language due to the higher social gap between the leader and the employee. Implications wise, leaders in Waqf institutions in Malaysia should consider developing a repertoire of language approaches to achieve positive organisational outcomes particularly in terms of management effectiveness.